Prognostic Evaluation of Feline Mammary Carcinomas: A Review of the Literature. (January 2015) - Zappulli, V.; Rasotto, R.; Caliari, D.; Mainenti, M.; Peña, L.; Goldschmidt, M. H.; Kiupel, M.
A large number of studies have investigated feline mammary tumors in an attempt to identify prognostic markers and generate comparative analyses with human breast cancer. Nevertheless, a retrospective base of assessments and the lack of standardization in methodology and study design have caused weakness in study results, making comparison difficult. We examined feline mammary tumor publications and evaluated postulated prognostic parameters according to the recently published "Recommended Guidelines for the Conduct and Evaluation of Prognostic Studies in Veterinary Oncology." Using these criteria, we determined with statistically significant reliability that prognostic parameters for feline mammary tumors are tumor grading and lymph node/lymphovascular invasion. Furthermore, tumor subtype, size, and staging are worthy of further standardized investigation. We present statistical significance for each studied parameter as well as its relevance to disease progression and survival. Our evaluation suggests that marker expression (ie, Ki67, HER2, ER) may provide relevant information applicable for therapeutic predictions; however, consensus efforts and protocol standardization are needed. We identify and discuss major points of concern—such as sample preservation and selection, standardization of immunohistochemical protocols, and evaluation of results—to provide support for subsequent reliable analyses.